Creating Customer Satisfaction Through Sensory Marketing: Study on the Foods and Beverage Industries in Bandung - Iston Dwija Utama (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2022)
This research aims to determine the influence of sensory marketing on customer satisfaction and the revisit intention of the food and beverage industries in Bandung, West Java, Indonesia. The study was conducted using quantitative methods through purposive sampling and the data will be processed using SMART-PLS tools. The study results showed an influence between sensory marketing on revisit intention that mediated customer satisfaction. Sensory marketing variables, the senses of sight, taste, and touch, were the most influential, while olfactory factors were insignificant in the study. The customer satisfaction variable that has the most influence is meeting customer needs and customer expectations. The managerial implication based on this research is that managers in the food and beverage industry should pay attention to the appearance of their products, maintain the taste of their products, and pay attention to the selection of materials in the store to meet the customer needs and customer expectations.